the Pelatihan Pembuatan Pupuk Kompos Sederhana Berbahan E-M4 Pada Kelompok Tani Bunga Padi Di Dusun Liba - Jusran, Jusran; Riski, Mohamad Iqbal; Suhardi, Suhardi (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2024)
Training on making simple compost fertilizer made from E-M4 for the Farmers group of Bunga Padi in Liba Hamlet was carried out as a form of implementing the tri dharma of higher education, namely service to the community. This activity was carried out in collaboration with the Farmers group of Bunga Padi in Liba Hamlet. The aim of this training was to provide training in making compost using the E-M4 decomposer by utilizing organic materials available in the environment. The materials used in this training include husks, straw, bran and cow dung. This training also involved students who were tasked with observing the development of the decomposition process from the time it was made until the material becomes compost. There were four observation variables, namely changes in temperature, texture, color and aroma of the compost material. The results of the observations showed that the decomposition process was going well and produced compost as expected. It was hoped that this training would provide new knowledge and skills for farmers in utilizing organic materials in their environment to make alternative fertilizers that were cheaper and more environmentally friendly.